2006
DOI: 10.2307/27641866
|View full text |Cite
|
Sign up to set email alerts
|

A Sequence of Polynomials for Approximating Arctangent

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Mathematical Association of America is collaborating with JSTOR to digitize, preserve and extend access to The American Mathematical Monthly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…It is, therefore, sufficient to approximate arctangent over the interval of [0, 1]. To this end, we use the technique introduced by Medina in [50] and its formal proof in [29]. In particular, [50] defines a sequence of polynomials over the input domain of [0, 1], denoted as h N (x), with the property that…”
Section: Compute ([Zmentioning
confidence: 99%
See 2 more Smart Citations
“…It is, therefore, sufficient to approximate arctangent over the interval of [0, 1]. To this end, we use the technique introduced by Medina in [50] and its formal proof in [29]. In particular, [50] defines a sequence of polynomials over the input domain of [0, 1], denoted as h N (x), with the property that…”
Section: Compute ([Zmentioning
confidence: 99%
“…This degree N is logarithmic with respect to the desired precision. Afterwards, the coefficients of h N (x) are computed from the recursive definitions in [50]. We choose this approach over other alternatives such as [33] for its efficiency.…”
Section: Compute ([Zmentioning
confidence: 99%
See 1 more Smart Citation
“…So it is of practical importance to use a polynomial approximation that converges more quickly to arctangent. A recent result of Medina's provides such an approximation [7], and this paper describes a formalization of that result in ACL2(r).…”
Section: Introductionmentioning
confidence: 95%
“…was recently studied in [Medina 2006], where it is shown that it can be used to produce polynomial approximations to arctan x on the interval [0, 1] whose error is governed by the size of the rational functions on that interval. In this section, we use these methods to produce polynomial approximations to arctan x on a smaller interval where the size of the integrand is much smaller, and hence the approximations converge much faster.…”
Section: Polynomial Approximations To Arctangentmentioning
confidence: 99%